El problema formas/vida y el estructuralismo vitalista de Jakob von Uexküll - Heredia, Juan Manuel (ARFIL y UNL, 2021)
The article analyzes the historical-conceptual sense that Jacob von Uexküll's theory assumes in contrast with forms/life problem that unfolds in the continental philosophy of the beginning of the 20th century. To this end, in first place, it reconstructs the epistemological configuration that presents the biological thought between 1890-1920, and introduces the neovitalist theory of Hans Driesch. Secondly, it analyses the emergence of the vitalist metaphysics of Henri Bergson and Georg Simmel, and poses the problem of the contradiction between forms and life. Finally, on the basis of the previous developments, it defends the thesis according to which Uexküll's work mobilizes a vitalist structuralism for which “Life equal to Form”.